Adding Voices to Physical Sciences Preservice Teachers' Approaches to Learning. Issue 2 (4th May 2019) - Chirikure, Tamirirofa; Govender, Nadaraj; Sibanda, Doras; Kolobe, Lebala; Good, Mary-Anne; Ngema, Sebenzile
Abstract : Students' approaches to learning have a significant impact on the outcomes of any educational programme. In the light of the documented concerns about the quality of students' engagement with academic work, this study sets out to determine and explain preservice teachers' (PSTs) approaches to learning. This was based on the premise that, while science teacher-educators may strive to inculcate a deep approach to learning in their PSTs, various contextual factors may impinge on these efforts. Ninety-four Physical Sciences PSTs' approaches to learning were explored through a survey questionnaire followed by 32 face-to-face interviews. The approaches to learning theory was used to develop the instruments and interpret the data. Mean agreement scores were used to determine the students' approaches to learning by profiling them based on a mean agreement scale. The findings indicated that most (68%) of the Physical Sciences PSTs tended to use combinatory pragmatic dissonant and deep-strategic approaches to learning. Several factors influenced the PSTs' approaches to learning but their socio-economic status and motivation to train as teachers seemed to have the greatest effect. It is imperative for lecturers to explore strategies to promote a deep approach to learning and high self-efficacy in students with low socio-economic status having to balance part-time work and studying. A more extensive study might help to ascertain the correlation between the motivation to train as teachers and students' approaches to learning.